Comparative effectiveness of teriflunomide and dimethyl fumarate: A nationwide cohort study. (16th April 2019) - Buron, Mathias Due; Chalmer, Thor Ameri; Sellebjerg, Finn; Frederiksen, Jette; Góra, Monika Katarzyna; Illes, Zsolt; Kant, Matthias; Mezei, Zsolt; Petersen, Thor; Rasmussen, Peter Vestergaard; Roshanisefat, Homayoun; Hassanpour-Kalam-Roudy, Houry; et al.
Abstract : Objective: To compare on-treatment efficacy and discontinuation outcomes in teriflunomide (TFL) and dimethyl fumarate (DMF) in the treatment of relapsing-remitting multiple sclerosis (RRMS) in a real-world setting. Methods: We identified all patients starting TFL or DMF from the Danish Multiple Sclerosis Registry and compared on-treatment efficacy outcomes between DMF using TFL, adjusted for clinical baseline variables and propensity score-based methods. Results: We included 2, 236 patients in the study: 1, 469 patients on TFL and 767 on DMF. Annualized relapse rates (ARRs) in TFL and DMF were 0.16 (95% confidence interval [CI] 0.13–0.20) and 0.09 (95% CI 0.07–0.12), respectively. Relapse rate ratio for DMF/TFL was 0.58 (95% CI 0.46–0.73, p < 0.001). DMF had a higher relapse-free survival proportion at 48 months of follow-up ( p < 0.05). We observed no difference in Expanded Disability Status Scale score worsening. Discontinuations due to disease breakthrough were 10.2% (95% CI 7.6%–12.8%) and 22.1% (95% CI 19.2%–25.0%) for DMF and TFL, respectively. A subgroup analysis of ARRs in 708 patients with available baseline MRI T2 lesion amount reported similar results after adjustment. Conclusion: We found lower ARR, higher relapse-free survival, and lower incidence of discontinuation due to disease breakthrough on treatment with DMF compared with TFL. Classification of evidence: This study provides Class II evidence that for patients with RRMS, DMF is more effective in preventing relapses and has lower discontinuation due to disease breakthrough compared with TFL.